Physics for the IB Diploma - Allum, John.; Morris, Paul, 1969- (London : Hodder Education, an Hachette UK Co., 2023)
A physics textbook that contains all Standard Level and Higher Level content for the IB Diploma and features extra chapters on graphs and data analysis and answering exam questions.
Includes index.
Young Adult
Young Adult
Keywords: International baccalaureate; Physics -- Textbooks; Physics -- Examinations -- Study guides; Physics -- Study and teaching (Secondary); International baccalaureate; Physics -- Textbooks; Physics -- Examinations -- Study guides; Physics -- Study and teaching; Study guides; Textbooks